Anticancer Activity Of Apis Dorsata Binghami Nest Extract From West Uluway, Tana Toraja District - Patandean, Selvrining; Mokosuli, Yermia Semuel; Ogi, Nova LIM; Djarang, Rievo H; Manampiring, Nonny; Moko, Emma Mauren (Universitas Negeri Manado, 2025)
Cancer is the leading cause of death in the world, with a high prevalence in Indonesia, especially breast cancer. Conventional therapies such as chemotherapy and radiotherapy have various limitations, including severe side effects and cancer cell resistance. This study aims to explore the anticancer potential of the ethanol extract of Apis dorsata Binghami nests originating from Uluway Barat Village, Tana Toraja Regency. Extraction was carried out using the maceration method with 96% ethanol solvent, with a yield of 51.42%, and bioactive compounds were identified through GC-MS analysis. Anticancer activity tests were carried out in vitro on MCF-7 breast cancer cells using the resazurin assay method . The results showed that the extract contained various bioactive compounds such as flavonoids, furanones, and aromatic aldehydes which are known to have antioxidant and anticancer activities. The IC50 value obtained was 434.30 µg/mL, indicating weak cytotoxic activity. Nevertheless, this extract showed significant ability to kill cancer cells at certain concentrations, especially 15.63 µg/mL which reduced cell viability by 44.39%. These results indicate that A. dorsata Binghami nests contain compounds that have the potential as natural anticancer agents, but require further research for fractionation and identification of more specific active compounds and further testing in vivo